Neutrophil extracellular traps (NETs) in immunity and diseases: second edition : editorial - Knopf, Jasmin (International journal of molecular sciences, 2025)
Neutrophils are the most abundant leucocytes in human blood and are the first responders at sites of inflammation or infection [...]
Gesehen am 09.09.2025